Characterizing the Role of the Rad5 Family of Proteins in DNA repair - Huang, Ada X. (Tufts Archival Research Center, 2020)
Rad5 is a protein that has been shown to impact recombination-mediated repair at CAG repeats. Interestingly, Rad5 is part of a larger family of proteins which are characterized by a SWI/SNF2 helicase motif interrupted by a RING finger domain, thus conferring chromatin remodeling capability. We show that Rad5, Irc20, Uls1, and Rad16 have significant roles in preventing CAG repeat fragility together and that Irc20 may have a compensatory relationship with Rad5 in certain model systems. Advisor: Dr. Catherine Freudenreich.